Physical activity prevalence and associated factors among Zimbabwean undergraduate students: A cross-sectional study. - Lynne T Makuzo; Paidamoyo Monalisa Chakandinakira; Ruramayi Nicole Shanu; Panashe Sithole; Israella H T Mugova; Leovellah Murape; Hardlife Muchinani; Isaac Munyoro; Shalom R Doyce; Tariro Dee Tunduwani; Clayton Zimunya; Beatrice K Shava; et al. (PLOS Global Public Health)
Many university students worldwide are physically inactive, negatively affecting their mental health and academic performance. Group-based physical activity (GBPA) can effectively increase physical activity levels. This study assessed the physical activity (PA) levels and related factors, knowledge, attitudes and perceptions of GBPA in a cross-sectional study of 1217 Zimbabwean undergraduates from three universities. Data were collected using the International Physical Activity Questionnaire (IPAQ), Exercise Benefits Barriers Scale (EBBS) and Knowledge, Attitudes and Perceptions (KAP) questionnaires. Data were analysed using logistic regression at α = 0.05. About 75.7% of the students engaged in moderate-to-high PA. Not playing sports [AOR 0.20;95%CI (.10 -.40)], a negative perception of exercise benefits [AOR 0.63;95%CI (.47 -.34)], studying a non-health program [AOR 1.4;95%CI (1.04- 1.94)], female [AOR 1.94;95%CI (1.45 - 2.56)], and first years (AOR 0.62; 95%CI (.43 -.91)] were associated with low PA. Only 41.9% reportedly engaged in GBPA. Not playing sports [AOR 3.06;95%CI (1.81; 5.17)] and negative perception of exercise benefits [AOR 2.69;95%CI (2.06; 3.50)] predicted low knowledge of GBPA. Lower PA levels [AOR:.684; 95% CI (.518;.903)], not playing sports [AOR 3.2 - 95%CI (1.92; 5.31)], negative perception of exercise benefits [AOR 3.34;95%CI (2.60:4.38)] and taking alcohol [AOR 0:63;95%CI (.48;.83)] were linked with negative attitudes and perceptions towards GBPA. While university students demonstrate high PA, knowledge, positive attitudes, and favourable perceptions toward GBPA, their participation in GBPA is low. Interventions targeting the promotion of GBPA among university students are necessary to achieve the benefits of physical activity.